2003
DOI: 10.1128/jcm.41.11.5153-5158.2003
|View full text |Cite
|
Sign up to set email alerts
|

Microarrays for Genotyping Human Group A Rotavirus by Multiplex Capture and Type-Specific Primer Extension

Abstract: Human group A rotavirus (HRV) is the major cause of severe gastroenteritis in infants worldwide. HRV shares the feature of a high degree of genetic diversity with many other RNA viruses, and therefore, genotyping of this organism is more complicated than genotyping of more stable DNA viruses. We describe a novel microarray-based method that allows high-throughput genotyping of RNA viruses with a high degree of polymorphism by multiplex capture and type-specific extension on microarrays. Denatured reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…These include type-specific PCR (20), restriction fragment length polymorphism (24), sequence analysis (3,5,10), capture and primer extension (32), and hybridization to oligonucleotide probes (7,43,44). …”
mentioning
confidence: 99%
“…These include type-specific PCR (20), restriction fragment length polymorphism (24), sequence analysis (3,5,10), capture and primer extension (32), and hybridization to oligonucleotide probes (7,43,44). …”
mentioning
confidence: 99%
“…By using a series of short probes, however, conserved regions of the genomes can still be sufficiently variable for characterization of enteric viruses. For example, Chizhikov, et al (2002) and Lovmar, et al (2003) used short probes (about 20 nucleotides in length) to successfully distinguish different rotavirus isolates.…”
Section: Discussionmentioning
confidence: 99%
“…A novel ArrayTube assay, which incorporates oligonucleotide DNA probes representing 24 of the most epidemiologically relevant O antigens and 47 H antigens, has been described for fast DNA serotyping of E. coli . Microarrays have also been used to characterize and type other gastroenteritis-causing viral pathogens including rotavirus, norovirus, and astrovirus (Chizhikov et al, 2002;Honma et al, 2007;Jaaskelainen and Maunula, 2006;Lovmar et al, 2003). Beyond diarrheal illnesses, Pas et al (2008) reported the comparison of reverse hybridization, microarray, and sequence analysis for hepatitis B virus (HBV) genotyping, suggesting that the InnoLipa HBV genotyping strip assay, a microarray-based system, detected dual infections and was an easy and quick tool for HBV genotyping.…”
Section: Comparative Genomics and Microbial Typingmentioning
confidence: 99%